An N-Terminal Missense Mutation in STX11 Causative of FHL4 Abrogates Syntaxin-11 Binding to Munc18-2 - Muller, Martha-Lena; Meeths, Marie; Chiang, Samuel; Tesi, Bianca; Entesarian, Miriam; Nilsson, Daniel; Wood, Stephanie M.; Nordenskjöld, Magnus; Henter, Jan-Inge; Naqvi, Ahmed; Bryceson, Yenan (Frontiers in Immunology, 2014)
Familial hemophagocytic lymphohistiocytosis (FHL) is an often-fatal hyperinflammatory disorder caused by autosomal recessive mutations in PRF1, UNC13D, STX11, and STXBP2. We identified a homozygous STX11 mutation, c.173T>C (p.L58P), in three patients presenting clinically with hemophagocytic lymphohistiocytosis from unrelated Pakistani families. The mutation yields an amino acid substitution in the N-terminal Habc domain of syntaxin-11 and resulted in defective NK cell degranulation. Notably, syntaxin-11 expression was decreased in patient cells. However, in an ectopic expression system, syntaxin-11 L58P was expressed at levels comparable to wild-type syntaxin-11, but did not bind Munc18-2. Moreover, another N-terminal syntaxin-11 mutant, R4A, also did not bind Munc18-2. Thus, we have identified a novel missense STX11 mutation causative of FHL type 4. The syntaxin-11 R4A and L58P mutations reveal that both the N-terminus and Habc domain of syntaxin-11 are required for binding to Munc18-2, implying similarity to the dynamic binary binding of neuronal syntaxin-1 to Munc18-1.